Engineering the Osmotic State of Pseudomonas putida KT2440 for Efficient Cell Disruption and Downstream Processing of Poly(3-Hydroxyalkanoates) - Poblete-Castro, Ignacio; Aravena-Carrasco, Carla; Orellana-Saez, Matias; Pacheco, Nicolás; Cabrera, Alex; Borrero-de Acuña, José Manuel (Frontiers in Bioengineering and Biotechnology, 2020)
In the last decade, the development of novel programmable cell lytic systems based on different inducible genetic constructs like the holin-endolysin and lysozyme appears as a promising alternative to circumvent the use of costly enzymes and mechanical disrupters for downstream processing of intracellular microbial products. Despite the advances, upon activation of these systems the cellular disruption of the biocatalyst occurs in an extended period, thus delaying the recovery of poly(3-hydroxyalkanoate) (PHA). Herein the osmotic state of Pseudomonas putida KT2440 was engineered by inactivating the inner-membrane residing rescue valve MscL, which is responsible mainly for circumventing low-osmolarity challenges. Then the major outer membrane porin OprF and the specific porin OprE were overproduced during PHA producing conditions on decanoate-grown cells. The engineered P. putida strains carrying each porin showed no impairment on growth rate and final biomass and PHA yield after 48 h cultivation. Expression of both porins in tandem in the mutant strain KTmscL-oprFE led to a slight reduction of the biomass synthesis (10%) but higher PHA accumulation (%wt) relative to the cell dry mass. Each strain was then challenged to an osmotic upshift for 1 h and subsequently to a rapid passage to a hypotonic condition where the membrane stability of the KTmscL-oprFE suffered damage, resulting in a rapid reduction of cell viability. Cell disruption accounted for more than 95% of the cell population within 3 hours as reported by colony forming units, FACS analyses, and transmission electron microscopy. PHA recovery yielded 94.2% of the biosynthesized biopolymer displaying no significant alterations on the final monomer composition. This study can serve as an efficient genetic platform for the recovery of any microbial intracellular compound allowing less unit operation steps for cellular disruption.